Gas exchange threshold in male speed-power versus endurance athletes ages 20-90 years - Kusy, K.; Krol-Zielinska, M.; Domaszewska, K.; Krysciak, J.; Podgórski, T.; Zielinski, J. (Medicine & Science in Sports & Exercise, 2012)
Purpose: This cross-sectional study compared the oxygen uptake at the gas exchange threshold (GET) and its relation to age between highly trained competitive speed-power athletes (SP), endurance athletes, and untrained participants.